CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (CSRD) DAN FINANCIAL SLACK TERHADAP KINERJA KEUANGAN - Abdillah, Pujangga; Regytha Aura Gunawan, Szabyna Regytha x; Suprapti, Suprapti; Suprayitno, Adi (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
The objective of this study is to examine CSRD (Corporate Social Responsibility Disclosure) and financial slack affect financial performance. The state of the global industry continues to develop, making the company’s business processes also develop. This economic progress is also accompanied by a decrease in environmental aspects with environmental damage in recent years. Disclosure of non-financial factors such as Corporate Social Responsibility (CSRD) indicators by companies aims to provide additional information about company performance that is not visible in annual report data or financial statements. The population of this study is the Indonesia Stock Exchange between 2020 to 2022. The sample of 768 observations was taken using a judgment sampling technique and quantitative approach. The findings of this study show that CSRD affects company performance as measured by Return on Assets (ROA). In other words, better CSRD standards can make companies perform better. The findings of this study also show that financial slack can improve company performance in the future. Keywords: Firm Performance, Financial Slack, CSRD